Reibungsgewinne – Reibungsverluste (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
Religion as a discontinued model – that is how the narrative of modernity likes to see it. Empirically, the situation is more complex: even if secularisation often makes religious institutions appear as losers, important areas of religion have proven to be innovative and productive. How, then, do gain and loss explain themselves in this frictional relationship? This is what the contributions to this volume explore using examples from different regions of global modernity. They are grouped around questions on which religions have worked particularly hard: the ethos of freedom in modernity, the challenges posed by modern sciences, the relationship to authority, new perspectives on one's own tradition and participation in 'modern' discourse. With contributions by Reiner Anselm | Martin Baumann | Reinhold Bernhardt | Anne Beutter | Amir Dziri | Silke Gülker | Michael Hochgeschwender | Frank Neubert | Almut-Barbara Renger | Valérie Rhein | Markus Ries | Erdal Toprakyaran | Andreas Tunger-Zanetti | Margit Wasmaier-Sailer